The role of inflammation in the association between gestational diabetes and obstructive sleep apnea: A pilot study. (December 2018) - Bublitz, MH; Carpenter, M; Amin, S; Okun, ML; Millman, R; De La Monte, SM; Bourjeily, G
Background: Obstructive sleep apnea is associated with pregnancy complications including gestational diabetes. Mechanisms underlying the association between obstructive sleep apnea and gestational diabetes remain to be elucidated. Methods: Twenty-three participants with gestational diabetes underwent home sleep apnea testing. Obstructive sleep apnea was defined as an apnea hypopnea index > 5. Fasting morning blood samples were measured using multianalyte profiling (xMAP) multiplexed bead array immunoassay for Interleukin 6, tumor necrosis factor-alpha, and Interleukin 8. Results: Age, body mass index, and gestational age at enrollment were 31 + 4.4 years, 35.7 + 7.4 kg/m 2, and 28 ± 4 weeks, respectively. Participants were 52% Caucasian and 16% had obstructive sleep apnea. We observed positive correlations between apnea hypopnea index and Interleukin 6 (r = 0.62, p = 0.005), Interleukin 8 (r = 0.56, p = .56), and tumor necrosis factor-alpha (r = .58, p = .009). Women with obstructive sleep apnea had higher levels of Interleukin 6 (F = 5.01, p = .037) and Interleukin 8 (F = 6.33, p = .021) vs. women without obstructive sleep apnea. Conclusion: These preliminary results indicate that in women with gestational diabetes, apnea hypopnea index is associated with an elevated inflammatory profile.